Reevaluating the -20° Astronomical Dawn Angle: An Islamic Jurisprudential and Astronomical Analysis of Subh Time Determination in South Sulawesi - Wahidin; Abd. Karim Faiz; Muh. Rasywan Syarif (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
The -20o dawn standard that applies in Indonesia has become a problem when the results of observations and research show that the appearance of dawn with the -20o standard is considered too fast. Based on this, researchers in this study conducted dawn observations in South Sulawesi at Aparalang Cliff in Bulukumba. The purpose of this study is to describe the method and basis of the Ministry of Religious Affairs of the Republic of Indonesia regarding the determination of dawn -20o. Second, to analyse the data of dawn appearance in Aparalang Cliff, Bulukumba, South Sulawesi based on digital image instrument. Third, to analyse the variation of dawn data from the perspective of wadh'i law. This research method is qualitative with observation at Aparalang Cliff with location specifications -5o 32' 14" (South latitude) and 120o 25' 50" (East longitude). The research time was conducted in July 2023. The result of this research is the government's provision of the Sun's position -20o below ufuq refers to the opinion of Ibn Yunus during the time of Al-Biruni, 958-1009 AD. Observation of dawn conducted on the cliff aparalang bulukumba South Sulawesi dawn (astronomical twilight) can be seen when the sun position -18o below ufuq. Fajr prayer time with a standard of -20o as determined by the government through the Ministry of Religious Affairs of the Republic of Indonesia is contrary to the concept of Wadh'i Law because the cause of the law does not yet exist in the condition of -20o.